The Wailing Wall - Fisher, Leonard Everett 1924- (Macmillan, 1989)
Surveys the history of the Jewish people in Palestine and their activities around the First and Second Temples the site of which is now marked by the Western or Wailing Wall, with an emphasis on events before 70 A.D.